The Changing Image of Islam in Japan: The Role of Civil Society in Disseminating better Information about Islam - Irma Rachmi Yulita; Susy Ong (Al-Jami'ah Research Centre, 2019)
This research focuses on the changing of image on Islam in Japan and the efforts of Japan’s civil society to eradicate Islam’s negative image created by Japan’s mass media. In preparation for the coming 2020 Olympic Games, the government, the local NGO, and even individual are taking initiatives to create a Muslim-friendly atmosphere. We try to look into their efforts to disseminate information, as well as to counter demagogues about Islam and Muslim. We have conducted in-depth interviews with 10 Muslims residing in Japan added with 2 respondents taken from book, and compared their stories with Japanese articles, books, and academic journals. Our conclusion is that despite the success in making Japanese society more amicable to foreign Muslims, the human relations problems within the Muslim community must take prioritize to improve the response of Japanese society.[Tulisan ini fokus pada perubahan citra Islam di Jepang dan usaha lembaga swadaya masyarakat (NGO) untuk mengurangi citra negatif Islam yang dibentuk oleh media massa Jepang. Menjelang pekan olahraga Olimpiade 2020, pemerintah, NGO lokal dan sebagian individu mengambil inisiatif menciptakan suasana yang ramah bagi muslim. Kami mengamati usaha mereka dalam merespon informasi yang menyudutkan agama Islam dan pemeluknya. Kami melakukan wawancara mendalam dengan 10 penduduk muslim di Jepang serta 2 informan literer. Kemudian kami membandingkan cerita mereka dengan berita, jurnal dan buku yang terbit di Jepang yang terkait dengan Islam. Meskipun mereka cukup berhasil meyakinkan masyarakat Jepang, tetapi persoalan hubungan antar sesama kelompok muslim perlu menjadi prioritas dalam rangka meningkatkan respon positif masyarakat Jepang.]